REMINERALIZING THERAPY IN THE PROCESS OF TEETH WHITENING - O.S. Kyrmanov; A.V. Lemeshko (Український стоматологічний альманах)
Resume. Nowadays, aesthetics plays an important role in dentistry due to the increased attention of people to the beauty and attractiveness of the smile, which is known as an effective tool in achieving both personal and professional purposes. Therefore, the whitening of discolored teeth is one of the promising directions in aesthetic dentistry. To date, there is much controversy among dentists about the effectiveness and, the most importantly, the safety of teeth whitening. The prevention of dentin hypersensitivity is among the main tasks associated with the safe and comfortable treatment and follow-up period for patients. In order to avoid the negative consequences of hyperesthesia, the teeth whitening procedure should be finished with remineralizing therapy. Thought there are a large number of techniques and products for the treatment of hyperesthesia, the question of their most appropriate selection and combination is remaining unresolved and is relevant to meet the steadily growing population demands.